PENGARUH PEMBERIAN KREDIT TERHADAP TINGKAT PENDAPATAN USAHA KECIL DAN MENENGAH (UKM) (STUDI KASUS PADA PT. BANK MANDIRI (PERSERO) Tbk.) - Rosalina Febrica Mayasari (JURNAL KOMPETITIF, 2014)
The objective of this research is to know the role of the People’s Business Credit for development of UKM in Palembang (Case Study of Bank Mandiri). The role is measured from income earned UKM enterpreneurs after getting help from People’s Business Credit of Bank Mandiri. The results showed that a significant capital for revenue growth of UKM in Palembang. Thus Ha is accepted, it means capital significant or significant impact on earnings UKM entrepreneurs at 95% confidence level. Key words: Capital, Loan and Micro, Small and Medium Enterprises (UKM)